1982
DOI: 10.1177/105960118200700410
|View full text |Cite
|
Sign up to set email alerts
|

Performance Rating Validity: The Relationship of Objective and Subjective Measures of Performance

Abstract: Substantial research has been conducted on how various factors such as personal traits of ratees and raters, organizational contexts, and rating format affect per formance ratings. However, a question receiving considerably less attention has been the degree to which actual differences in job performance account for variations in performance ratings. This study examined the relationship be tween subjective and objective performance measures for vocational/rehabilita tion counselors. No relationship was found b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 18 publications
1
33
0
Order By: Relevance
“…Nisbett and Wilson's (1977) research on the &dquo;halo effect&dquo; also lends support to the argument that liking has an important role in evaluation of other people. Further, performance-appraisal research has found liking to be an important factor in supervisory ratings of subordinates (Alexander & Wilkins, 1982;Cardy & Dobbins, 1986;Dipboye, 1985). Collectively, the preceding research suggests that leaders' liking for subordinates could easily have a major influence on their decisions about the nature of exchange they initiate with a member.…”
Section: Role Of the Initial Interactionmentioning
confidence: 91%
“…Nisbett and Wilson's (1977) research on the &dquo;halo effect&dquo; also lends support to the argument that liking has an important role in evaluation of other people. Further, performance-appraisal research has found liking to be an important factor in supervisory ratings of subordinates (Alexander & Wilkins, 1982;Cardy & Dobbins, 1986;Dipboye, 1985). Collectively, the preceding research suggests that leaders' liking for subordinates could easily have a major influence on their decisions about the nature of exchange they initiate with a member.…”
Section: Role Of the Initial Interactionmentioning
confidence: 91%
“…The study showed that stress levels of medical personnel were higher in departments where more claims were reported. Since subjective performance measures are vulnerable to perceptual distortion, they are often very weakly related to objective measures (Alexander and Wilkins 1982). Especially in ICUs such poor relationships might be expected, since nurses' perception of unit performance is based on direct observations that are likely to be biased.…”
Section: 2mentioning
confidence: 99%
“…For individual nurses it is impossible to collect and analyse all data that are necessary to assess their unit's objective performance. Nevertheless, objective and subjective performance are not completely unrelated, because it can be expected that a unit's objective performance is reflected to a certain extent by nurses' subjective performance and vice versa (Alexander andWilkins 1982, Hoffman et al 1991).…”
Section: Subjective and Objective Performance Indicatorsmentioning
confidence: 99%
“…As the Hunters note (personal communication), objective performance measures are not easy to derive, particularly for managerial roles. Nevertheless, in light of work on the accuracy of supervisory ratings (Alexander and Wilkins, 1982;Heneman, 1986), efforts must be made to move away from such proxies. Promising work in this area has been provided by Kritzman (1986), in the case of in vestment analysts, and by Weekley and Gier (1987), using sales performance.…”
Section: Exhibit 2 Studying the Relationship Between Selection Researmentioning
confidence: 99%